Pengumbaran Aib di Media Sosial Perspektif Qur’an:: Kajian Double Movement Fazlur Rahman - Nurusshobah, Nurusshobah; Said, Muhammad; Asiah, Siti (STAI Darul Kamal NW Kembang Kerang, 2023)
Al-Qur'an is a holy book that is always needed to answer life's problems, from the past to the end of time. Contemporary applications aimed at information, communication and showcasing skills. However, the problems they face are increasingly complex and experiencing developments, such as the problem of venting (indulgence of disgrace) on social media. Therefore, a new method is needed in understanding the Al-Quran so that it can be contextualized and can provide the best solution. This study examines the verses of vent (indulgence of disgrace), the author uses the understanding method offered by Fazlur Rahman's Double Movement theory as an analytical knife which is considered capable of answering contemporary problems, by looking at the socio-historical problem as a way to find a moral idea. Al-Quran verses so that they can be understood and applied to the present context. This research uses a type of library research (library research), is qualitative in nature with the presentation of data in a descriptive-analytical manner. The results of the analysis show that venting is dishonorable on social media, firstly the value of moral ideas in QS. ar- Ra'ad verse 10, QS. An-Nur verse 19 explains the prohibition of indulgence and talking about one's own disgrace. Second, QS. An-Nisa- verse 148 QS.al-Hujurat verse 12 and QS. An-Nisa verse 34 indulges in other people's disgrace. Third, An-Nahl verse 43, that venting (indulgence of disgrace) is permissible in the sense that an effort to solve a problem is included in the obligation, provided that with intention, it is conveyed to get a solution (intention, finding a solution) and delivered to someone who can provide a solution ( experts), as the moral ideals of the Qur'an that are relevant to the context of today's contemporary society.